Water Supply System Of Ancient And Medieval Samarkand - Sadikova Sitora-bonu Nematjonovna, Sirojiddinov Uktam Samaridinovich Hasanova Hafiza Bahriddinovna (International Journal of Advanced Science and Technology, 2020)
The article highlights the unique features of the traditional water supply of Samarkand in antiquity and the Middle Ages. Being part of the architectural and landscape structure of the city, the water supply system, which is a complex network of irrigation ditches and houzs, was inextricably linked with the social, cultural, religious life of medieval Samarkand. The article narrates as an ancient, original, ten-century-old water supply system of Samarkand has been changing through the centuries to the present day under the influence of the development of civilization.